The Federal Role in the Innocence Movement in America - Findley, Keith A. (Journal of contemporary criminal justice, 2017)
Despite its small contribution to the ranks of the exonerated, and more broadly its relatively small share of all criminal cases, the federal government has played a distinct and important role in fostering and shaping the innocence movement. This article recounts the various ways in which the federal government has done so: through high-profile measures to recognize the reality of wrongful convictions, direct funding of innocence work, use of federal purse strings to shape criminal justice policy, setting an example through legislation on matters as diverse as access to postconviction DNA testing and compensating the wrongly convicted, and leadership on issues such as the problems with the forensic sciences. The article concludes that, moving forward, the committed involvement of the federal government will remain important, especially in tackling such challenging problems as flawed forensic sciences and ensuring financial resources for innocence advocates.